Аналіз принципів контейнерного управління на базі системи Kubernetes - Приходько, О. С. (ХНУРЕ, 2024)
A key solution used for service orchestration is Kubernetes, an opensource software for automating the deployment, scaling and management of containerized applications. At the core of Kubernetes is container technology, which is made up of Docker containers. A container is a small virtual machine that performs one simple task, meaning it actually implements a single microservice. The aggregate of microservices forms a microservice platform. The paper makes a detailed analysis of Kubernetes system architecture, its components and services. The options of traffic management between multiple microservices of Kubernetes container platform with the help of Istio are analyzed.
Keywords: контейнерне управління; Kubernetes